2021
DOI: 10.1097/meg.0000000000002154
|View full text |Cite
|
Sign up to set email alerts
|

Midodrine and albumin versus albumin alone for the secondary prophylaxis of acute kidney injury in a patient with cirrhosis and ascites

Abstract: Background Acute kidney injury (AKI) in a patient with cirrhosis has high short-term mortality. Midodrine has shown promising results in the treatment of AKI-hepatorenal syndrome (HRS-AKI). Aims To compare midodrine and albumin versus albumin alone for the secondary prophylaxis of HRS-AKI. Patients and method Open labeled, nonrandomized, pilot study. Patients with a diagnosis of HRS-AKI were recruited after complete recovery. Patients were given midodrine daily (15 mg) and injection albumin infusion 20 g w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Studies on long-term HAS administration have shown variable results [72,[91][92][93][94]. Long-term HAS administration (for outpatients) can prevent SBP and non-SBP related infections and reduce the incidence of kidney dysfunction [72,94,95]. Long-term HAS can also prevent hospital admissions, ascites recurrence, and prolong survival [72,91,92,94].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on long-term HAS administration have shown variable results [72,[91][92][93][94]. Long-term HAS administration (for outpatients) can prevent SBP and non-SBP related infections and reduce the incidence of kidney dysfunction [72,94,95]. Long-term HAS can also prevent hospital admissions, ascites recurrence, and prolong survival [72,91,92,94].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…72 91 92 93 94 Long-term HAS administration (for outpatients) can prevent SBP- and non-SBP–related infections and reduce the incidence of kidney dysfunction. 72 94 95 Long-term HAS can also prevent hospital admissions, ascites recurrence, and prolong survival. 72 91 92 94 In addition, long-term albumin administration has an immunomodulatory effect in patients with decompensated cirrhosis.…”
Section: Primary Preventionmentioning
confidence: 99%